Ocean soup : tide pool poems - Swinburne, Stephen R.; Peterson, Mary (Watertown, Mass. : Charlesbridge, 2010)
Playful poems and information about some of the creatures that live in Atlantic and Pacific Ocean tide pools.
Includes bibliographical references.
008-012
NP
Accelerated Reader AR
Keywords: Tide pool animals -- Juvenile literature; Tide pool animals -- Juvenile poetry; Children's poetry, American